Acute‐Phase Response Following Different Modalities of Non‐Surgical Periodontal Treatment in Subjects Affected by Periodontitis and Co‐Morbid Hypertension: A Randomised Clinical Trial. - Petrini, Morena; Gennai, Stefano; Marruganti, Crystal; Marhl, Urska; Izzetti, Rossana; Nisi, Marco; Graziani, Filippo (Journal of Clinical Periodontology, 2026)
Aim: To compare acute‐phase response and blood pressure levels following full‐mouth or quadrant non‐surgical periodontal treatment (FM‐SRP or Q‐SRP) in patients affected by hypertension and periodontitis. Patients and Methods: Forty patients affected by hypertension and periodontitis were enrolled and randomly allocated to either the FM‐SRP or Q‐SRP group. Periodontal parameters were registered at baseline and 3 months after treatment. Blood samples and vital signs were collected at baseline, 24 h and 3 months after treatment. Primary outcomes were high‐sensitivity C‐reactive protein (hs‐CRP) concentration 24 h post operation and the variation in levels of blood pressure (BP). Results: Significant increase in hs‐CRP levels was observed at 24 h, with FM‐SRP presenting higher values than Q‐SRP (p < 0.05). In terms of periodontal outcomes, both treatment regimens proved equally effective. Systolic BP was significantly reduced at days 1 and 90 in both groups (p < 0.01), while a 90‐day significant decrease in diastolic BP was detected only in the Q‐SRP group (p < 0.01). Multiple regression analysis suggests that the peak of hs‐CRP at 24 h may influence BP reduction at Day 90. Conclusions: Q‐SRP may be preferred in patients affected by hypertension and periodontitis, as a higher post‐operative inflammatory response was associated with lower improvements in BP control in the medium term.